Pendampingan Pentas Seni Berbasis Projek Merdeka Belajar bagi Siswa SDN 4 dan SDN 6 Metro Timur - Alfarisi; Ade Gunawan; Andi Widiono; Adya Rosa Prasasti; Titin Sarwendah; Fikriana; Bobi Hidayat (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community‑service program implemented a project‑based art performance mentoring model for elementary students of SD 4 and SD 6 Metro Timur from 13 June to 13 July 2025. The one‑month program consisted of (1) needs analysis, (2) on‑site coaching clinics in each school, and (3) a culminating “Gelar Karya” showcase at Universitas Muhammadiyah Metro. Mixed‑method evaluation combining observation sheets, interviews, and a creativity rubric indicated (a) a 42 % increase in students’ self‑confidence scores, (b) improved collaboration between teachers and university mentors, and (c) the production of multidisciplinary artifacts (drama, books, local‑food products) aligned with the Merdeka Belajar framework. The model proves effective in cultivating 6C competencies and can be replicated in other schools with minimal cost.